Husserl’s Phenomenology and Scientific Positivism - Guillermo (Estudios de Filosofía, 2018)
Edmund Husserl criticizes scientific positivism because it reduces the meaning of the world of life, as if this world consisted in a set of instrumentally manipulatable objects, while hiding a subjectivity operative at the levels of both science and pre-scientific experience. The return to the world of life (Lebenswelt) as a universal context of meanings and an inexhaustible source of resources to validate the pretenses of truth, normativeness and truthfulness of the subject, allows phenomenology to genetically reconstruct the meaning of science, technic and technology as an ethically and responsibly determinable human activity.